Toxicity analysis of food contaminants based on network toxicology and molecular docking: A case study of Zearalenone - Xiaobo Xu; RuiLi Miao; Ping Xu; Leishan Chen; Kun Zhao; PingHui Xu; Hanna Fotina (PLoS ONE, 2026)
Zearalenone (ZEA) is a non – steroid estrogen contaminant produced by fungi of the genus Fusarium. It is widely present in grains and seriously threatens global food safety. This study takes ZEA as an example to effectively evaluate the toxicity of food contaminants through network toxicology, molecular docking and molecular dynamics simulation strategies, and analyzes the molecular mechanism of its hypothesized toxicity – nephrotoxicity. The study found that ZEA affects immunotoxicity, inflammatory response, apoptosis, and cytogenetic mutations by regulating core targets such as STAT3, ESR1, HSP90AA1, MMP9, and MTOR, and regulating pathways such as the cancer pathway and the PI3K - Akt signaling pathway, ultimately leading to nephrotoxicity. The results of molecular docking and molecular dynamics simulation also showed good binding affinity between ZEA and core targets. This result provided a theoretical basis for understanding the molecular mechanism of ZEA – nephrotoxicity and for preventing and treating cancers caused by the food contaminant ZEA. In addition, the methods of network toxicology and molecular docking also provided an effective way to rapidly evaluate the toxicity of food contaminants, effectively addressing the cost and ethical issues associated with the use of experimental animals.